2020
DOI: 10.3311/ppci.16888
|View full text |Cite
|
Sign up to set email alerts
|

Shape Optimization to Reduce Wind Pressure on the Surfaces of a Rectangular Building with Horizontal Limbs

Abstract: The present study consists of shape optimization of a rectangular plan shaped tall building with horizontal limbs under wind attack, which would minimize the wind pressure on all the faces of the building model simultaneously. For the purpose, the external pressure coefficients on different faces of the building (Cpe) are selected as the objective functions. The position of the limbs and the wind incidence angle are taken as design variables. The design of experiment (DOE) is done using random sampling. The va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…They made experimental measurements and CFD analysis. Paul and Dalui (2021) studied shape optimization of a rectangular plan shaped tall building with horizontal limbs under wind attack, which would minimize the wind pressure on all the faces of the building model simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…They made experimental measurements and CFD analysis. Paul and Dalui (2021) studied shape optimization of a rectangular plan shaped tall building with horizontal limbs under wind attack, which would minimize the wind pressure on all the faces of the building model simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Building dimension and ratio of buildings' height to width and thickness also has a significant influence on wind distribution and characteristics, as suggested by Mou et al [9]. Applying horizontal limps in building plans as studied by [10] showed to be effective in minimizing external wind pressure on building faces. Tapering and setback are amongst the popular major aerodynamic modifications in tall buildings to lessen wind responses.…”
Section: Introductionmentioning
confidence: 93%
“…Several numerical and experimental studies have investigated the effect of global (major) and local (minor) modifications on tall building wind responses. Considering major modifications, different building plan configurations showed a strong relation to wind structural responses [6][7][8][9][10]. Hayashida et al [6] studied multiple building plan configuration to examine wind-induced dynamic response of building and found that triangular and 'Y'-shaped building plans counter smaller responses of structural displacement in comparison to rectangular plans.…”
Section: Introductionmentioning
confidence: 99%
“…CFD technique gives the wind effects on various shapes of high-rise buildings in quick time; it works by dividing the building geometry into small elements using meshing, and a number of studies have been carried out on various shapes, for example, Bhattacharyya and Dalui [26] on "E" shape, Raj et al [27] on "H" shape, He and Song [28] on TTU building, Yu and Kareem [29] and Sanyal and Dalui [30] on rectangular shape, Paul and Dalui [31] and Okajima et al [32] on rectangular shape with horizontal limbs, Paul and Dalui [33] on "+" shape, Hajra and Dalui [34] on octagonal shape, Gaur and Raj [35] on square model, Bairagi and Dalui [36] on stepped building model, and Sanyal and Dalui [37][38][39][40] on "Y" shape building model. e major findings obtained through the numerical simulation are as follows: results obtained through the numerical simulation are significantly affected by the mesh size, pressure distributed on the building model depends on the height of the building model, velocity alteration is found on the roof of the building model, and the drag force depends on the exposure to wind.…”
Section: Introductionmentioning
confidence: 99%